Evalusai Kinerja Simpang Tak Bersinyal (Study Kasus Simpang Jalan Sukomulyo dan Jalan Kyai H. Syafii Kec. Manyar Kab. Gresik) - Ardianto, Rudi; Hepiyanto, Rasio (Jurnal Talenta Sipil, 2024)
The intersection of Jalan Sukomulyo and Jalan Kyai H. Syafii is one of the 3 unsignalized intersections with quite high traffic levels. So it is necessary to conduct research on the performance of the intersection. This type of research was conducted using field observation methods. The primary data collection is done by making direct observations at the Sukomulyo road intersection and Kyai H. Syafii road. The LHR survey was carried out for one week by directly recording vehicles passing through the planning location at 15-minute intervals. When the data have been obtained, it analyzed based on the Directorate General of Highways MKJI 1997. The results of the analysis of the performance of the intersection at the Sukomulyo road intersection and Kyai H. Syafii road show quite good results even though many vehicles pass it. Morning traffic volume is 4220.8 pcu/hour, afternoon is 2071.6 pcu/hour, in the afternoon is 3741.3 pcu/hour. The morning intersection capacity is 6552.74 pcu/hour, the afternoon is 4805.38 pcu/hour, in the afternoon is 5500.06 pcu/hour. The degree of saturation in the morning is 0.64, afternoon is 0.43 and afternoon is 0.68. Morning delay is 7.79 seconds/hour, afternoon is 3.98 seconds/hour, in the afternoon is 8.57 seconds/hour. Probability of queuing in the morning with an upper limit of 35.22% and lower limit of 16.98%, Probability of queuing in the afternoon with an upper limit of 20.44% and a lower limit of 8.5%, Probability of queuing in the afternoon with an upper limit of 38.78% and a lower limit of 18.98% .